2022
DOI: 10.1093/gastro/goac023
|View full text |Cite
|
Sign up to set email alerts
|

Can a single-port robot be safely used for robotic total gastrectomy for advanced gastric cancer? First experience using the da Vinci SP platform

Abstract: Background Many studies have shown the operative feasibility and safety of robotic gastrectomy. Surgeons are pursuing single-port (SP) surgery to leverage the advantages of minimally invasive gastrectomy. The purpose of this study was to describe technical considerations and short-term outcomes from the first reported SP robotic total gastrectomy (RTG) using the da Vinci SP platform. Methods A 75-year-old patient with a body-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Among the included studies, 36 were case reports [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], 52 were noncomparative studies [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ,…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 36 were case reports [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], 52 were noncomparative studies [ 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ,…”
Section: Resultsmentioning
confidence: 99%
“…Successful case reports of robotic total gastrectomy (RTG) for locally progressive gastric cancer using the da Vinci SP platform establish the feasibility of SP robotic application for total gastrectomy. 1 The SHURUI SP surgical robot is a new robot platform. At present, the robot has only been approved for marketing by the National Medical Products Administration of China, and its safety and efficacy for radical prostatectomy have been proven.…”
Section: Introductionmentioning
confidence: 99%
“…However, single‐port (SP) robots have been developed to achieve less surgical trauma and more aesthetically pleasing surgical incisions. Successful case reports of robotic total gastrectomy (RTG) for locally progressive gastric cancer using the da Vinci SP platform establish the feasibility of SP robotic application for total gastrectomy 1 . The SHURUI SP surgical robot is a new robot platform.…”
Section: Introductionmentioning
confidence: 99%
“…Minimally invasive gastrectomy (MIG) has several advantages such as smaller surgical incision and faster post-operative recovery [ 9 ]. Most studies also demonstrated the comparable short-term and long-term outcomes between MIG and open gastrectomy (OG) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%